Do Immigrants Spur Offshoring? Firm-Level Evidence - Andreas Hatzigeorgiou; Patrik Karpaty; Richard Kneller; Magnus Lodefalk (Örebro University School of Business, 2016)
Offshoring is an important aspect of firms' internationalization. However, offshoring comes at a cost, especially where information or trust is lacking. Immigrant employees could reduce such offshoring costs through their knowledge of their former home countries and via access to foreign networks. We develop a framework of heterogeneous final-good firms to guide our empirical analysis and draw on new employer-employee data for approximately 12,000 Swedish firms during the time period 1998-2007. Our results support the hypothesis that immigrant employees spur offshoring activities by firms through lower offshoring costs. Hiring one additional foreign-born worker can increase offshoring up to three percent on average, with skilled migrants having the strongest effects.
Keywords: D21; D83; F14; F22; F23; 330; offshoring; migration; networks; trust; information; trade barriers